2014
DOI: 10.1007/s40615-014-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Age-Related Variations of Testosterone Levels Among US Males: Potential Implications for Prostate Cancer and Personalized Medication

Abstract: Aim The magnitude of the age-related declines in testosterone rather than levels measured at single point in time may be related to the genesis of prostate cancer (PCa). We examined age-related variations of testosterone levels among black and white males, which may provide important insights into racial disparities in PCa incidence and mortality. Method We analyzed data from the 1999-2004 National Health and Nutritional Examination Survey to compare agerelated variations in the testosterone levels of 355 blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…This finding is also in accordance with some epidemiological evidence. According to one study based on National Health and Nutritional Examination Survey (NHANES) data, black males, compared to white males, have significantly higher peak levels of testosterone during young age, but the difference diminishes with aging and completely disappears after age 60. It indicated that the testosterone levels in blacks decrease faster with increasing age compared to that in white.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is also in accordance with some epidemiological evidence. According to one study based on National Health and Nutritional Examination Survey (NHANES) data, black males, compared to white males, have significantly higher peak levels of testosterone during young age, but the difference diminishes with aging and completely disappears after age 60. It indicated that the testosterone levels in blacks decrease faster with increasing age compared to that in white.…”
Section: Discussionsupporting
confidence: 92%
“…Based on this knowledge, measures that can slow age-related declines in serum testosterone can potentially be applied to prevent PCa, such as engaging in more physical activity, controlling body weight, supplementing zinc and preventing vitamin D deficiency, et al 30,31 These will be of particular importance from the age of 40, when serum testosterone is about to have an obvious decline. 29,32 Second, this will potentially endow positive significance on testosterone replacement therapy (TRT) in preventing PCa, as TRT can effectively smooth the age-related decline in testosterone if given at appropriate time. This is in line with a recent prospective study reporting that TRT among hypogonadal men had preventive effect against PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic patients are treated with systemic therapy only, and that was mainly Androgen Deprivation Treatment (ADT) until recently. There is some evidence to suggest that African American men have higher testosterone and androgen receptor expression compared to white men (21,63,64). These might be contributing to a better response to ADT, which in turn might nullify other socio-economic factors contributing to the disparities in the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 One study in adolescents showed Mexican-Americans to have the highest testosterone compared to non-Hispanic Whites, and non-Hispanic Blacks 12 and another showed that Blacks had a higher level of testosterone only in the age category 20-39. 14 While some studies have shown no difference, 15 a recent meta-analysis compared sex-steroid hormone concentration in black and white men and found that black men had a slightly significant higher level of free testosterone. 16 Identified racial differences in semen parameters and hormones may be genetic, due to sociodemographic factors but also due to dietary and/or cultural differences.…”
Section: Punjani Et Al Effect Of Ethnicity On Semen and Hormonal Parametersmentioning
confidence: 99%